Factores sociodemográficos, estilos de vida y comorbilidad asociados a sobrepeso y obesidad en personal de salud del Hospital Iquitos, 2024 - Vela Vargas, Frida Valeria (2024)
Objective: To determine the association between sociodemographic factors, lifestyles, and comorbidity with overweight and obesity in health personnel at the Iquitos Hospital, 2024. Methodology: Quantitative, observational, analytical, cross sectional study that surveyed, measured, and weighed 265 health workers. Results: 46.42% of participants were overweight and 30.94% were obese, with grade I obesity being the most prevalent (20.75%). The Poisson regression result showed that healthcare workers aged 30-59 years had a higher prevalence of overweight than patients aged 18-29 years (PR: 2.01; 95% CI: 1.05-3.87; p=0.036). Those who had a healthy lifestyle had a lower prevalence of obesity (PRa: 0.53; 95% CI: 0.31-0.91; p=0.020) and overweight (PRa: 0.37; 95% CI: 0.15-0.90;p<0.001). Having at least one comorbidity was associated with obesity (p =0.006). Arterial hypertension increased the prevalence of overweight (PRa: 1.52; 95% CI:1.10-2.31; p=0.048) and obesity (PRa: 2.34; 95% CI: 1.44-3.79; p=0.001). Dyslipidemia and asthma increased the prevalence of obesity (PRa: 1.57; 95% CI:1.12-2.18; p= 0.007) and (PRa: 1.50; 95% CI: 1.13-1.99; p= 0.004) respectively. Conclusions: The study revealed a high rate of overweight and obesity in health personnel. Age, lifestyles, arterial hypertension, dyslipidemia and asthma were associated factors. These findings seem to show an emerging problem in health personnel, increasing the need for urgent actions to address these disorders.